CHA2DS2-VASc Score as a Predictor of New-Onset Atrial Fibrillation After Catheter Ablation of Typical Atrial Flutter - Liu, Fei; Xin, Zechang; Bin Waleed, Khalid; Lin, Yajuan; Tse, Gary; Luhanga, Andrew; Sun, Yuanjun; Gao, Lianjun; Yin, Xiaomeng; Xia, Yunlong (Frontiers in Physiology, 2020)
Purpose: Cavotricuspid isthmus (CTI) ablation is an effective procedure for typical atrial flutter (AFL), but patients remain at an elevated risk for developing new atrial fibrillation (AF). Currently, there is limited data on the utility of CHA2DS2-VASc score to predict new-onset AF after typical AFL ablation. In this study, we assessed whether the CHA2DS2-VASc score is a useful predictor of new-onset AF after CTI ablation in typical AFL patients without a prior history of AF. Methods: This was a retrospective study of 103 typical AFL patients with no prior history of AF, who underwent successful CTI ablation. The endpoint was occurrence of new-onset AF during follow-up. Results: During a mean follow-up period of 24.6±16.9 months, at least one episode of AF occurred in 33(32%) patients. Multivariate Cox regression analysis revealed that CHA2DS2-VASc score (hazard ratio 1.736; 95% confidence interval 1.370–2.201; P <0.001) was significantly associated with postablation new-onset AF (area under the curve: 0.797). A cut-off value of 3 stratified these patients into two groups with different incidence of postablation new-onset AF (67.9% vs. 18.7%, P＜0 .001). Conclusion: The CHA2DS2-VASc score is a useful tool for the prediction of new-onset AF after ablation of typical AFL. Patients with CHA2DS2-VASc score ≥3 are more likely to develop new-onset AF and should be monitored more closely.